Single-Shot Volumetric Imaging Using Optical Projection Tomography - Darling,C; Davis,SPX; Kumar,S; French,PMW; McGinty,J (2021)
We present a single-shot volumetric imaging method, utilising optical projection tomography. We record projections simultaneously, implementing compressive sensing and machine learning to record up to 70 (camera limited) 1x1x1.9mm volumes/second.